(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Surgical site infection (SSI) is one of the most common postoperative complications following abdominal surgery and contributes significantly to postoperative morbidity, prolonged hospital stay, and increased healthcare costs. Emergency laparotomy procedures carry a particularly high risk of infection because of contamination from gastrointestinal flora and the urgent nature of the surgery.¹² Aim: To evaluate the microbiological profile of organisms isolated from surgical site infections following emergency laparotomy in a tertiary care teaching hospital. Methods: A prospective observational study was conducted on 150 patients undergoing emergency laparotomy at a tertiary care teaching hospital. Patients who developed clinical features of surgical site infection underwent wound swab culture and sensitivity testing to identify the causative organisms. Data were analyzed using descriptive statistical methods. Results: Out of 150 patients, 40 patients (26.7%) developed surgical site infections. The most frequently isolated organism was Escherichia coli (35%), followed by Klebsiella pneumoniae (20%), methicillin-resistant Staphylococcus aureus (MRSA) (15%), Pseudomonas aeruginosa (12.5%), Enterococcus faecalis (10%), and coagulase-negative Staphylococci (7.5%). Gram-negative organisms constituted 67.5% of isolates, whereas gram-positive organisms accounted for 32.5%. Conclusion: Gram-negative organisms, particularly Escherichia coli, were the most common pathogens responsible for surgical site infections following emergency laparotomy. Understanding the microbiological spectrum of SSI is essential for guiding empirical antibiotic therapy and improving postoperative outcomes.